Tactile Experience Induces c-fos Expression in Rat Barrel Cortex - Filipkowski, Robert K. (Cold Spring Harbor Laboratory Press, 2000)
Understanding gene expression that is responsive to sensory stimulation is central to elucidate molecular mechanisms underlying neuronal plasticity. In this study we demonstrate two new methods of stimulating whiskers that provide major sensory input to rat neocortex. In the first paradigm, animals were placed on the top of a cylinder and their vibrissae were brushed by hand. In the second paradigm, animals were placed for a brief period of time into a new, wired cage resulting in vibrissae stimulation when they explored the new environment. Both approaches induced c-Fos expression in barrel cortex corresponding to the stimulated vibrissae, especially in layer IV. Layers II/III and V/VI also showed c-Fos induction, but there were no detectable changes in layer VIb. The majority of c-Fos-expressing cells are probably not inhibitory neurons, because they do not show parvalbumin staining. Both paradigms, in contrast to the previous methods, are simple to use and do not require anesthesia, restraint of animals, or elaborate experimental setups.